1995
DOI: 10.1073/pnas.92.15.7125
|View full text |Cite
|
Sign up to set email alerts
|

Enhancers increase the probability but not the level of gene expression.

Abstract: We have studied enhancer function in transient and stable expression assays in mammalian cells by using systems that distinguish expressing from The mechanism by which enhancers activate transcription remains a subject for speculation. One proposed mode of enhancer action is to increase the rate of transcription from a linked promoter (Fig. 1A). This "rate" model is based on nuclear run-on assays of populations of cells transiently transfected with plasmid constructs, which found that more nascent transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
194
1
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(226 citation statements)
references
References 27 publications
30
194
1
1
Order By: Relevance
“…In these experiments, expression from a simple enhancer-promoter-reporter gene combination randomly integrated as a single copy gene into the host genome was examined on the single cell level. 24,25 It was found that in the absence of selection the stability of expression, not the expression level, was differentially modulated by chromatin-mediated genomic position effects. Expression was progressively silenced after multiple rounds of cell division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these experiments, expression from a simple enhancer-promoter-reporter gene combination randomly integrated as a single copy gene into the host genome was examined on the single cell level. 24,25 It was found that in the absence of selection the stability of expression, not the expression level, was differentially modulated by chromatin-mediated genomic position effects. Expression was progressively silenced after multiple rounds of cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Such a stochastic behaviour of gene expression driven by simple enhancer-promoter combinations has been observed in other systems and can be molecularly explained by a differential stability of transcription factor complexes. 24,25 The second model would predict that expression would not only be silenced, but would also be switched on again. We therefore studied the develop-a c b 32 …”
Section: Recombinant Hvs Expresses Transgenes Throughout the Entire Ementioning
confidence: 99%
“…This observation is in favor of the binary model by which enhancers act by increasing the probability of a transgene being active, but not the level of expression per template. 39 This model predicts that, at a defined integration site, expression would be more stable, but not higher, in the presence of an active enhancer. 40 In this context, the results obtained by the analysis of the transduced PLB985 clones indicate that the MoMuLV LTR is much less efficient than the FMEV LTR in counteracting the suppression imposed on provirus gene expression in the hematopoietic cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of mRNA molecules increases, so does the predictability of the number of proteins synthesized per cell. Likewise, if the number of enhancer and transcription activator molecules in a cell is low, large variation in mRNA copy number is expected (Walters et al 1995;McAdams and Arkin 1997;Fiering et al 2000;Elowitz et al 2002;Raser and O'Shea 2004). These effects may account for the large cell-to-cell variations observed in isogenic cell populations (Levsky and Singer 2003;Peixoto et al 2004).…”
mentioning
confidence: 99%